Studies on Antarctic Krill Euphausia superba - Biochemical and Processing Aspects - C.N., Ravishanker; K., Ashok Kumar; A.G., Radhakrishnan (Fishery Technology, 2025)
Antarctic krill, harvested from Southern ocean during the first Indian Antarctic krill expedition, was processed on board FORV Sagar Sampada. Changes in biochemical parameters during frozen storage were studied. Various products were prepared from the mince obtained from krill. The chemical composition was similar to other related species. Fluoride in the shell migrated into the meat on frozen storage to the tune of 44% after three months.